Resistance to permethrin in Aedes aegypti (L.) in Northern México. - Flores Suárez, Adriana Elizabeth; Reyes Solis, Guadalupe del Carmen; Fernández Salas, Ildefonso; Sánches Ramos, Francisco J.; Ponce García, Gustavo (Southwestern Entomological Society, 2009)
Diagnostic dose (DD) of permethrin was determined in Aedes aegypti (L.), from three states (Coahuila, Sonora, and Tamaulipas) in northern Mexico. After exposing 10 groups of 100 females to the DD obtained and producing 50% mortality, individuals were divided into two categories: survivors and dead. Mosquitoes in each of these categories were dissected to separate the head, thorax, and abdomen. Biochemical tests were done on the head and thorax to determine activity by resistance-related enzymes including: α and β-esterases, mixed-function oxidases (MFOs), glutathione-S-transferase (GST) and insensitive acetyl cholinesterase (iAChE). Results were compared with those for a susceptible strain of Ae. aegypti from New Orleans. A population from Coahuila showed iAChE as the only enzyme activity that surpassed the threshold established with the susceptible strain, however, this mechanism is not associated with resistance to pyrethroids, but rather with resistance to organophosphate and carbamate insecticides. For the populations from Tamaulipas, none of the mechanisms studied were important in conferring resistance to permethrin. MFOs were present at elevated levels of activity, appearing as the main detoxifying mechanism, in the population from Sonoita, Sonora state.